Structural and Magnetic Properties of Nickel Substituted Mg Ferrites. (2017) - Chavan, Pradeep; Naik, L R; Chavan, Geeta; Belavi, P B; Kotnala, R K
Abstract: Polycrystalline ferrites with general formula Nix Mg1-x Fe2 O4 (0.0 ≤ x≤ 0.5) were synthesized by solid state reaction method. The existence of cubic spinel structure of ferrites was confirmed by X-ray diffraction (XRD) measurement which belongs to the space group of Fd3m - Oh 7 . Crystallite size of ferrites was estimated by using Debye-Scherer formula; it varies from 930 nm to 1.04 μm. The lattice constant, interplanar distances and miller indices were estimated by using X-ray diffraction measurement. The lattice constant increases with increase in Ni content. Porosity of ferrites was estimated by using Hendricks and Adams method; it is found to increase with increase in Ni content and maximum porosity 22.4% was observed for Ni0.5 Mg0.5 Fe2 O4 ferrites. The dielectric constant decreases with increase in frequency shows dielectric dispersion behavior which is predicted by Maxwell-Wagner type interfacial polarization and is in good agreement with Koops phenomenological theory. AC conductivity increases with increase in frequency shows small polarons type of conduction mechanism. The magnetic properties of ferrites were studied by using M-H hysteresis loop and measured saturation magnetization and magnetic moment of the ferrites.